Muzaki's Perception of Zakah Policy as Income Tax Deduction in Situbondo Regency - Maulidha Ayu Andini; N. Ari Subagio; Agus Mahardiyanto; Umi Cholifah (Universitas Wahid Hasyim Semarang, 2022)
This study aims to determine the partial and simultaneous effect of halal-haram aspects, legal awareness, and religiosity on the zakah policy as a deduction from income tax in Situbondo Regency. By using a quantitative method of sampling using purposive sampling techniques and quota sampling. Data collection using a questionnaire. The data analysis technique used is instrument test, classical assumption test, and multiple linear regression. The results of the research show that the Halal-haram Aspect, Legal Awareness, and Religiosity have a significant simultaneous effect on Muzaki's Perception of Zakah Policy as a Deduction for Income Tax in Situbondo Regency. Meanwhile, the results of the partial test, the Halal-haram Aspect variable and Legal Awareness have a significant influence on Muzaki's Perceptions, but the legal awareness variable has no significant effect on Muzaki's Perceptions.